Gender commonalities and differences in the neural processing of visual sexual stimuli - Wehrum, Sina; Klucken, Tim; Kagerer, Sabine; Walter, Bertram; Hermann, Andrea; Vaitl, Dieter; Stark, Rudolf (Journal of sexual medicine, 2013)
Few studies so far have directly compared the neural processing of visual sexual stimuli in men and women. Also, most of these studies only compared sexual with neutral stimuli, making it difficult to disentangle sexual stimulus processing from general emotional processing. The current study aimed to explore gender commonalities and differences in neural activity associated with the processing of visual sexual stimuli in a large sample of 50 men and 50 women. In order to disentangle effects of sexual processing from those of general emotional processing, we employed sexual, neutral, positive, and negative emotional pictures. Subjects passively viewed sexual, neutral, positive, and negative emotional pictures during a functional magnetic resonance imaging (fMRI) session. Pictures were presented in 24 blocks of five pictures each. Every block was rated immediately after its presentation with respect to valence, arousal, and sexual arousal. Blood oxygen level dependent responses measured by fMRI and subjective ratings. fMRI analysis revealed a distributed network for the neural processing of sexual stimuli comprising the hypothalamus, the nucleus accumbens, as well as orbitofrontal, occipital, and parietal areas. This network could be identified (i) for both men and women, with men showing overall stronger activations than women and (ii) independent of general emotional arousal or valence effects. Our data speak in favor of a common neural network associated with the processing of visual sexual stimuli in men and women. Apart from the observed gender commonalities, overall stronger responses in men were observed that might indicate stronger sexual responsivity in men.